Соціальна відповідальність у ланцюгах постачання підприємств цементної промисловості: міжнародний вимір - Oliinyk, Olena O. (Institute of Industrial Economics of NAS of Ukraine, 2026)
The purpose of this article is to examine approaches to socially responsible supply chain management in the cement industry based on a content analysis of corporate documents issued by the world’s largest cement producers. It has been determined that cooperation with suppliers based on the principles of social responsibility has a direct positive impact on the financial performance of a cement company. This finding underscores the crucial role of institutional mechanisms of control, standardisation, and alignment of requirements within supply chains. A content analysis of supplier codes of conduct of Holcim, Heidelberg Materials and CRH was carried out using the text analytics tools of Voyant Tools. The results revealed substantial differences in semantic emphases, regulatory strictness and approaches to integrating corporate social responsibility into supply chain management. Holcim adheres to a socio-ethical model that combines managerial standards with a strong focus on workers’ rights and a corporate culture of integrity. Heidelberg Materials follows a normative-legal model built on strict compliance with international conventions, labour standards and technical environmental regulations. CRH demonstrates a process- and stakeholder-oriented model dominated by sustainability, risk management and due diligence. Despite a shared regulatory foundation, each document demonstrates its own emphases, which shape the company’s distinctive “social responsibility profile”. Taken together, these approaches reflect the spectrum of contemporary responsible sourcing practices in the cement industry and demonstrate how global companies are institutionalizing CSR in their interactions with their counterparties. The practical value of the study lies in deepening the understanding of mechanisms for shaping socially responsible supply chains in the cement industry, which can be used to improve corporate policies and enhance the resilience of supply chains.